Superstructure optimization of bioethanol production from corn stover - Siti Syahirah, Azizan; Nur Farisha Irwayu, Effendy; Zainatul Bahiyah, Handani (IOP Publishing Ltd, 2019)
Bioethanol is a liquid fuel that can be produced from various raw materials. The first generation of bioethanol which are starch and sugar has begun to decline as these materials are considered to be the food sources for human as well as animals. However, the rise of production of bioethanol from the second generation which are the lignocellulosic materials has been proven to give a lot of benefits to mankind instead. Various technologies were studied in order to develop a systematic approach for designing an optimal processing route for bioethanol production from lignocellulosic biomass. A superstructure on the available process technologies which include the three main technologies, the pretreatment, sugar conversion, separation and purification was first developed before screening it down to a final superstructure. All of the data to be used in this study were collected from open literature and followed by the selection and development of the models required in order to solve the generic models and problems by using an optimization software, the Generic Algebraic Modelling System (GAMS). The results of software GAMS indicate that the optimal processing route in producing bioethanol from lignocellulosic biomass include the technologies of steam explosion, dilute acid followed by fermentation, beer and dehydration of ethanol on zeolite for each process interval